(untitled) (Eurasian Journal of Ecology, 2019)
The mutagenic activity of carbon dioxide (CO2) on the mutant soybean line T-219 (Glycine max (L.) Merrill), in which the synthesis of chlorophyll depends on the allelic state of the gene, was studied. The dominant allele Y11 causes a dark green plant, and the recessive allele y11 causes a golden yellow plant. We examined the level of somatic mutations by the presence of light green spots on dark green leaves and yellow spots on light green leaves (direct mutation Y11 → y11), light green spots on golden yellow leaves (reverse mutation y11 → Y11). Methyl methanesulfonate (MMS), a direct-acting mutagen, was used as a positive control. Soybean seeds, treated with MMS for 24 hours, were germinated under standard laboratory conditions and conditions of high CO2 concentration (5000 ppm) in a specialized box with adjustable CO2 content. In plants grown under high CO2 concentration, the frequency of leaf somatic mutations was at the control level. However, in plants whose seeds were treated in MMS and grown under standard laboratory conditions, the total number of spots per leaf statistically significantly increased 4.3 times (p<0.05). When treating seeds with a mutagen followed by cultivation under high CO 2 concentration, the total number of spots per leaf increased 6.3 times (p<0.001) compared with the control and 14.1 times (p<0.001) compared with the cultivation variant high CO2 concentration. Revealed co-mutagenic effect of CO2 when combined with the mutagen. The impact of CO2 on the morphophysiological parameters of plants, the height and rate of photosynthesis, has been studied. On the 10th day of the experiment, the highest plant growth was under high CO2 concentration and was 7.60±0.92 cm. In plants grown under standard conditions (control), the height of plants was 1.4 times lower (p<0.05). When treating seeds with MMS, followed by germination both under normal conditions and with high CO2 concentration, plant height was at the control level. However, the accelerated growth of plants under high CO2 concentration was observed only during the first two weeks, then they died. The rate of photosynthesis in conditions of high CO2 level increased by 2.0 times, but the difference is not statistically significant. When growing plants at high CO2 concentrations, photosynthesis intensity increased 2.0 times compared with the control, but the difference was not statistically significant. In plants grown from seeds treated with MMS, the rate of photosynthesis was 1.7 times lower (p<0.05) compared with the control, but when grown under high CO2 concentration, it increased 1.6 times. At the same time, the rate of photosynthesis decreased 2.2 times (p<0.05) in comparison with the control. A correlation analysis was made between the values of the studied morphophysiological parameters of experimental soybean plants. The correlation coefficient was r = 0.91, which indicates a high positive correlation between the rate of photosynthesis and the plant height. Thus, CO2 did not show mutagenic activity on the mutant soybean line T-219. However, the combined action of CO2 and the classic mutagen MMS a statistically significant increased the frequency of mutations of the gene responsible for the chlorophyll synthesis. The results obtained indicate the ability of carbon dioxide to co-mutagenic action. Key words: soybean, carbon dioxide, mutation, comutagen, chlorophyll, mutant line.